Fabrication and Characterization of PVC-Based Nanofiber Membranes for Water Filtration Application - Sosiati, Harini; Ramadhan, Fachri; Rahman, M. Budi Nur (Semesta Teknika, 2023)
Polyvinyl chloride (PVC) dissolved in N-dimethylacetamide (DMAC) and filled with polyvinyl pyrrolidone (PVP) has been studied for water treatment applications due to the material being hydrophobic, rigid, and biodegradable. However, it does not have antibacterial properties. The chitosan nanoparticles (CSNPs) as a natural antibacterial polymer are added into PEO/PVC blend to fabricate nanofiber membranes for well water filtration. We investigate the effects of adding PEO and CSNPs to PVC on the morphology, tensile properties, water contact angle, and water filtration efficiency of the nanofiber membranes. The PEO-PVC polymer solutions are dissolved in DMAC by varying concentrations of 0, 1, 2, 3, and 4% PEO (w/w), then fabricated to be the nanofiber membranes by the electrospinning technique. The PEO/PVC membrane’s contact angle decreases with the PEO concentration and by adding 1% CSNPs. This trend aligns with the average nanofiber diameter but is opposite to the tensile strength. The 1% CSNPs/4% PEO/PVC membrane has shown 78% and 92% efficiency in filtering Coliform and Colitinja bacteria in the well water, respectively.